Fotografia e resistência na ocupação Novo Amanhecer : existe o indivíduo em sociedade? - Santana, Diego Bragança de (2016)
In this paper, we aim to understand how the social actors of a community on the outskirts of Aracaju, Sergipe, and sighted policy practiced in their daily lives. These analyzes are guided by research on memory, enunciated through the narratives tessitura, which emerged through interviews by former residents. From these statements, it was possible to identify the direction of the trajectory of these subjects in a time and space that is configured through preterit symbolic procedurals that therefore allowed us to understand how to have relationships between the discourses, identities, self representation, engagement and communication. Given the above, we chose to use as anthropological analysis method, Photoethnography and ethnography of cyberspace, added the collection and comparison of the information obtained from the filtering of documentary sources.